CAMPUS UNIVERSITARIOS COMO AGENTES DE LA EDUCACIÓN PARA LA SOSTENIBILIDAD AMBIENTAL (Biocenosis, 2015)
A review of various actions performed in universities of Costa Rica and other countries in search of a culture of environmental sustainability on their campuses is presented. Some of them are: the establishment of environmental policies, environmental axis incorporation into curricula and institutional environmental management programs. Some indicators to monitor these actions are also included.
Keywords: Environmental sustainability; University environmental culture; Environmental Education